1994
DOI: 10.1113/jphysiol.1994.sp020146
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of outward Na(+)‐Ca2+ exchange current in guinea‐pig ventricular myocytes.

Abstract: 4. With 100 mm cytoplasmic Na+ and no extracellular Na+ (replaced with 140mm Li+), application of extracellular Ca2+ was predicted to reorient exchanger binding sites from the extracellular side to the cytoplasmic side and thereby favour inactivation. During such protocols, the outward exchange current decayed by 60-80 % when activated by extracellular Ca2+. The current decayed similarly when extracellular Ca2+ and Na+ were applied together, whereby current magnitudes were about 3-fold smaller. 5. The decay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 31 publications
1
73
1
Order By: Relevance
“…Several studies were designed to resolve this problem. Hilgemann and colleagues (11,12,27,28) investigated the question by measuring NCX1 currents in giant excised patches. The work used two preparations, NCX1-expressing Xenopus oocytes (27) or cardiac myocytes expressing native NCX1 (11,12,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were designed to resolve this problem. Hilgemann and colleagues (11,12,27,28) investigated the question by measuring NCX1 currents in giant excised patches. The work used two preparations, NCX1-expressing Xenopus oocytes (27) or cardiac myocytes expressing native NCX1 (11,12,28).…”
mentioning
confidence: 99%
“…Hilgemann and colleagues (11,12,27,28) investigated the question by measuring NCX1 currents in giant excised patches. The work used two preparations, NCX1-expressing Xenopus oocytes (27) or cardiac myocytes expressing native NCX1 (11,12,28). These investigations found no functional change in cardiac NCX1 activity following application of PKA or protein kinase C (PKC) catalytic subunits to the intracellular side of the giant patch.…”
mentioning
confidence: 99%
“…Our study actually demonstrated that the increase in active NCX, which was caused by the attenuation of inactivation, is the major cause of the increase, although the inactivation (I 1 and I 2 inactivation) [28,36,37] could not be distinguished by the present protocol. Concomitant changes in other proteins, such as PLM, might also be related to the attenuation, but the underlying mechanisms need to be further clarified.…”
Section: Discussionmentioning
confidence: 87%
“…6a). The intrinsic inactivation mechanisms of NCX1 [28,36,37] was assessed in a manner similar to a previous study [28] in Fig 6b. Slower inactivation of I NCX was observed in myocytes from HYP, suggesting the attenuation of inactivation mechanisms. The mean time constant of I NCX inactivation in HYP myocytes (n = 7) was significantly larger than that in CONT myocytes (n = 4) (11.4 ± 1.6 s vs. 8.4 ± 1.2 s) (Fig.…”
Section: Collagen Accumulationmentioning
confidence: 99%
See 1 more Smart Citation